Exploring the pathways model in a sample of patients with gambling disorder - Mestre-Bach, Gemma; Granero, Roser; Fernández-Aranda, Fernando; Potenza, Marc N.; Jiménez-Murcia, Susana (International gambling studies, 2022)
From clinical and research perspectives, the Pathways Model has been supported in adolescent and adult populations as a theoretical explanatory framework for considering gambling disorder (GD). However, it has been less well explored in clinical samples. Therefore, the aim of this study was to explore the Pathways Model, specifically pathways 2 (emotionally vulnerable) and 3 (antisocial impulsivist), in 241 consecutive treatment-seeking adults with GD. Structural equation modeling was used. Path analyses that considered continuous variables provided, in general, support for the Pathways Model in this clinical population, albeit with some caveats. The results suggest the presence of different profiles of gamblers, with some having emotions and others impulsivity-related factors more prominently involved. Additional associations, not raised by the model, were also found. For example, a greater role for anxiety as compared with depression was observed in pathway 2, and important mediating roles for cognitive distortions and habituation were observed across pathways. Using an approach that considered variables dimensionally may help aid in understanding clinically relevant relationships. The current findings suggest complexities regarding relationships between factors involved in GD clinical samples. These findings have implications for characterizing subtypes of GD and development of optimal prevention and treatment approaches.
Keywords: gambling; impulsivity; addictive behavior; depression; substance abuse; JCR; Scopus